Achieving a durable economy: Lessons learned from Burlington, Vermont. Issue 1 (2nd January 2020) - Seifer, Bruce; Antczak, Ed; Phillips, Rhonda
ABSTRACT: In this case, an overview is provided of the innovative economic and community development approaches that the City of Burlington, Vermont has used over several decades to create a more sustainable economy. A description of the six sectors of a durable economy discusses locally focused, cultural, social, inclusive, political, and environmental/sustainable aspects. Lessons learned about various initiatives used to foster a more durable economy are presented to conclude the case.